Coordination processes in partnerships between German governmental organizations and German sports federations in jointly implemented SDP projects - Schreiner, Laura; Kastrup, Valerie; Mayer, Jochen (Frontiers in Sports and Active Living, 2022)
Sports and physical activity are increasingly used as instruments of development policy. Within this field of sport for development and peace (SDP), one can observe a large number of partnerships between national governmental organizations and national sport federations. These are particularly important although these organizations pursue different core objectives with their SDP engagement. The aim of this qualitative study is to analyze how German governmental organizations and sports federations coordinate jointly managed SDP projects. Against the backdrop of systems theory, we conducted interviews with participants from relevant organizations. The qualitative content analysis revealed that inter-organizational coordination takes place partly in hierarchical and partly in network-based structures. The results show complex patterns between the participating organizations which gain varying degrees of influence on the SDP projects and seek to get specific resources through the cooperations. These should be taken into consideration when designing SDP projects to build stable cooperations that bring all the participating organizations an added value.